2016
DOI: 10.1007/s10096-016-2575-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of septic shock and severe infections in migrants and returning travelers requiring critical care

Abstract: During the past decade, global human movement created a virtually "borderless world". Consequently, the developed world is facing "forgotten" and now imported infectious diseases. Many infections are observed upon travel and migration, and the clinical spectrum is diverse, ranging from asymptomatic infection to severe septic shock. The severity of infection depends on the etiology and timeliness of diagnosis. While assessing the etiology of severe infection in travelers and migrants, it is important to acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Infections may become clinically apparent after long latency periods and recommended diagnostic tools include culture (special media), tissue biopsies, serology and polymerase chain reaction from bone marrow and peripheral blood 16 . Recent reports indicate that visceral leishmaniasis has become a frequent cause of critical illness in migrants and returning travellers 17 . Indeed, we recently treated a young migrant from Eritrea with septic shock.…”
Section: Parasitic Infections In the Intensive Care Unitmentioning
confidence: 99%
“…Infections may become clinically apparent after long latency periods and recommended diagnostic tools include culture (special media), tissue biopsies, serology and polymerase chain reaction from bone marrow and peripheral blood 16 . Recent reports indicate that visceral leishmaniasis has become a frequent cause of critical illness in migrants and returning travellers 17 . Indeed, we recently treated a young migrant from Eritrea with septic shock.…”
Section: Parasitic Infections In the Intensive Care Unitmentioning
confidence: 99%
“…Poor living conditions, including living in open fields, has resulted in the deterioration in health of many individuals and numerous serious medical problems. 2,3 Some studies have been reported in the literature, referring to refugees acquiring diseases requiring ICU admission, or highlighting specific infections in refugees. 4,5 In general medical practice, patients with CA infectious diseases comprise 20% of the cases in ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…Traveling and population dynamics have caused intensified spreading of communicable diseases. Many infections have been diagnosed during and after travel and migration, along with the fact that there is a large number of Turkish communities living across Europe who could carry these infectious clones while visiting Turkey [21]. More observational studies are required in order to investigate European and other epidemic clones with hospitals across bordering cities and areas closer to Syria and Iraq.…”
Section: Discussionmentioning
confidence: 99%